Effectiveness of combined use of misoprostol with intracervical catheter for induction of labour: a randomized control trial - Ferdausi, Munira; Rahman, Aurin; Geeti, Shahreen; Shoma Chockroborty, Shinthia; Zaman, Nasreen; Siddika, Ayesha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Labor induction methods are continuously evolving to ensure safer and more effective outcomes for both mother and neonate. The present study aimed to assess the effectiveness and safety of combined use of misoprostol with intracervical catheter for labor induction. Methods: This single-blinded, parallel-group randomized control trial conducted at Shaheed Suhrawardy Medical College, Dhaka, Bangladesh, included 200 women with term gestation and Bishop score ≤6. Participants were divided into two groups: the intervention group (group B) received misoprostol juice and Foley’s catheter, while the control group (group A) received misoprostol in the posterior fornix. Results: In Group A, 58% had vaginal deliveries, while in Group B, 65% had vaginal deliveries. Group B experienced a longer mean length of labor in the 1st stage (13.25±1.095) compared to Group A (12.98±1.982, p=0.008). The 3rd stage was shorter for Group B (10.00±0.000) than Group A (12.02±2.469, p<0.001). The most common induction reason was labor pain with an unfavorable cervix (31 in Group A and 33 in Group B). Group B had a higher percentage of inductions at less than 12 hours and a lower percentage at more than 24 hours. Neonatal outcomes were generally better for Group B. The Cox regression hazard model showed a lower likelihood of positive outcomes in Group B (hazard ratio 0.337, 95% CI 0.243-0.469, p=0.000), indicating a statistically significant difference between the groups. Conclusions: The combined use of misoprostol with Foley’s catheter for labor induction is safe and effective, resulting in shorter labor duration and higher rates of vaginal delivery compared to misoprostol alone.